2013
DOI: 10.1007/s00464-013-2863-1
|View full text |Cite
|
Sign up to set email alerts
|

Robotic thyroidectomy by bilateral axillo-breast approach: review of 1026 cases and surgical completeness

Abstract: BABA RoT is a safe and effective method that provides good surgical completeness and has low rates of postoperative complications and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 41 publications
1
100
0
5
Order By: Relevance
“…5 Other studies found that sTg levels at the first RAI treatment were similar in patients who underwent BABA RT and OT. 3,6,7,9,11 sTg levels at diagnostic whole body scan after RAI ablation were also similar in patients who underwent BABA RT and OT (1.01±2.16 vs. 1.17±3.73, p=0.778 ), 13,14 as was RAI uptake rate at the first whole body scan (11.1% vs. 5.9%, p=0.564).…”
Section: Stimulated Thyroglobulin Levelmentioning
confidence: 92%
See 4 more Smart Citations
“…5 Other studies found that sTg levels at the first RAI treatment were similar in patients who underwent BABA RT and OT. 3,6,7,9,11 sTg levels at diagnostic whole body scan after RAI ablation were also similar in patients who underwent BABA RT and OT (1.01±2.16 vs. 1.17±3.73, p=0.778 ), 13,14 as was RAI uptake rate at the first whole body scan (11.1% vs. 5.9%, p=0.564).…”
Section: Stimulated Thyroglobulin Levelmentioning
confidence: 92%
“…Permanent RLN injury was observed in 0.2% of patients in one study, but not in other studies. [5][6][7][8][9][10] In addition, rates of transient and permanent RLN injury did not differ significantly in patients undergoing BABA RT and OT. [6][7][8][9]11 In BABA RT, intraoperative neuromonitoring (IONM) has been used to identify the RLN and to assess vocal cord function.…”
Section: Recurrent Laryngeal Nerve Injurymentioning
confidence: 99%
See 3 more Smart Citations